2006
DOI: 10.1104/pp.106.079046
|View full text |Cite
|
Sign up to set email alerts
|

A Conserved Mechanism Controls Translation of Rubisco Large Subunit in Different Photosynthetic Organisms

Abstract: We previously proposed a mechanism for control of Rubisco expression and assembly during oxidative stress in Chlamydomonas reinhardtii. The N terminus of the large subunit (LSU) comprises an RNA recognition motif (RRM) that is normally buried in the protein, but becomes exposed under oxidizing conditions when the glutathione pool shifts toward its oxidized form. Thus, de novo translation and assembly of Rubisco LSU stop with similar kinetics and the unpaired small subunit (SSU) is rapidly degraded. Here we sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
63
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 41 publications
1
63
0
Order By: Relevance
“…Light stress generates reactive oxygen species, which can reversibly or irreversibly inactivate Rubisco. It was recently shown that methyl viologen-induced oxidative stress leads to inhibition of LS synthesis in tobacco and the purple bacterium Rhodospirillum rubrum (20), as previously shown for Chlamydomonas (34). Because Rhodospirillum lacks the SS, LS translational regulation must be SS-independent, as we have concluded is the case in tobacco.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Light stress generates reactive oxygen species, which can reversibly or irreversibly inactivate Rubisco. It was recently shown that methyl viologen-induced oxidative stress leads to inhibition of LS synthesis in tobacco and the purple bacterium Rhodospirillum rubrum (20), as previously shown for Chlamydomonas (34). Because Rhodospirillum lacks the SS, LS translational regulation must be SS-independent, as we have concluded is the case in tobacco.…”
Section: Discussionmentioning
confidence: 79%
“…Alternatively, repression may parallel bacterial ribosomal protein feedback regulation, where a direct interaction between the protein and its cognate RNA is observed (30). Interestingly, gel mobility shift assays reveal an LS N-terminal domain RNA-binding activity under oxidizing conditions, although this activity is nonspecific (20,31). The regulatory significance of this domain remains to be tested in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It comprises an RNA recognition motif that becomes exposed under oxidizing conditions when the glutathione pool shifts toward its oxidized form (Cohen, Sapir, & Shapira, 2006). The oxygen sensitivity of the N‐terminus, and its role binding to RNA, may play an evolutionarily significant role in regulating Rubisco expression (Cohen et al., 2006; Kapralov & Filatov, 2007; Yosef et al., 2004). Regulation of expression can attenuate acute physiological response to perturbation inside or outside the cell (Bailey, 1991; Berry, Mure, & Yerramsetty, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…For these reasons, it is possible that this substitutional enrichment associated with the N‐terminus may reflect an initial adaptive attempt to cope with increasing oxidative stress prior to the GOE. (Cohen et al., 2006). …”
Section: Discussionmentioning
confidence: 99%